2017
DOI: 10.3390/rs9040293
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Physical and Chemical Properties by Visible and Near-Infrared Diffuse Reflectance Spectroscopy in the Central Amazon

Abstract: Visible and near-infrared diffuse reflectance spectroscopy (VIS-NIR) has shown levels of accuracy comparable to conventional laboratory methods for estimating soil properties. Soil chemical and physical properties have been predicted by reflectance spectroscopy successfully on subtropical and temperate soils, whereas soils from tropical agro-forest regions have received less attention, especially those from tropical rainforests. A spectral characterization provides a proficient pathway for soil characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 41 publications
10
52
1
2
Order By: Relevance
“…However, SDSG decreased model performance of the remaining multivariate models for the two soil properties studied. These results with spectral derivatives and ensemble-learning algorithms (RF) are in agreement with Vasques et al (2008), Pinheiro et al (2017), Dotto et al (2018), and Santana et al (2018).…”
Section: Effects Of the Preprocessing Techniques On Modelingsupporting
confidence: 73%
“…However, SDSG decreased model performance of the remaining multivariate models for the two soil properties studied. These results with spectral derivatives and ensemble-learning algorithms (RF) are in agreement with Vasques et al (2008), Pinheiro et al (2017), Dotto et al (2018), and Santana et al (2018).…”
Section: Effects Of the Preprocessing Techniques On Modelingsupporting
confidence: 73%
“…The root mean square error and regression coefficients obtained from the PLRS analysis of this study showed that with three latent vectors selected, 74% of the variation of SOC content was explained by this model (R 2 = 0.74), the RPD of 1.47 indicates an acceptable prediction, that could be improved using more samples. Conforti et al [35] found more accurate predictions (R 2 = 0.84; RPD = 2.53) in soils over gneiss and schists; other studies [72] show more similar results (R 2 = 0.71; RPD = 1.84) for acid heterogeneous soils in the Central Amazon region. After searching for publications on the estimation of soil characteristics by VIS/NIR spectroscopy in gypsiferous areas, only a similar approach was found in the study of Babaeian et al [73].…”
Section: Discussionmentioning
confidence: 87%
“…To solve this problem, downsampling is applied to band 8 of every single date imagery to achieve the spatial resolution of 30m. PLSR is a particular form of multivariate linear regression (Wang et al, 2018),which is the most common method used in soil properties prediction (Pinheiro et al, 2017). PLSR is underpinned by the assumption that the dependent variable can be estimated via a linear combination of explanatory variables.The maximum number of latent variables in PLSR is set at 20 and the optimum number of latent variables are determined by 5-fold cross-validation.…”
Section: Satellite Datamentioning
confidence: 99%